Application of SEM and Petrographic Studies to Reservoir Characterisation of the Eze-Aku Sandstone (Afikpo Sub-basin), South-eastern Nigeria - Ejeh, Omabehere Innocent; Odigi, Minapuye Isaac (Iraqi Journal of Science, 2022)
The reservoir characteristics of the Pre-Santonian Eze-Aku sandstone were assessed using an integrated thin section petrography and SEM Back-Scattered Electron (BSE) imaging methods. Fresh outcrop data were collected in the Afikpo area (SE Nigeria). Twenty-eight representative samples from the different localities were analysed to obtain mineralogical and petrographical datasets germane for reservoir characterisation. Thin section petrography indicates that the sandstones are medium-grained, have an average Q90F10L0 modal composition, and are classified as mainly sub-arkose. The sandstones on SEM reveal the presence of cement in the form of quartz overgrowths, authigenic clays and feldspar. From epoxy-stained thin sections and/or SEM BSE image analysis, primary, secondary (inferred from partial to total feldspar dissolution/alteration), and micro- (in authigenic clays) porosity types were identified. Although the development of quartz overgrowths, authigenic clay precipitation, and feldspar dissolution often affect reservoir properties of sandstone negatively, the Eze-Aku sandstones still retained very good reservoir properties (porosity, average 22.7 %; permeability, average 745.43 mD). This can be attributed to the abundance of framework grains that have been stabilized by quartz cement and relatively limited feldspar dissolution. The stabilized framework grains help preserve reservoir characteristics and resist further compaction beyond eogenetic depths. The feldspar dissolution produced silica and aluminium that was precipitated to form the quartz overgrowths and the authigenic clays (e.g., kaolinite), respectively. The relatively concurrent precipitation of silica and aluminium from dissolution products reduces the quartz overgrowth quantity and authigenic clays that could have adversely affected the reservoir characteristics.